Dollarization and Foreign Exchange Rate Volatility in Nigeria: The Role of Institutional Quality - Silva Opuala-Charles; Jonah Orji (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The study examined the nexus between dollarization and exchange rate volatility with the role of institutional quality for the period 1981 to 2021. The Granger Causality Approach was used to forecast the relationship between the variables. The Findings showed a unidirectional causality from cross border currency exposure to increase in dollarization which in turn influences exchange rate volatility and exacts inflationary pressure in Nigeria. The study, also showed that; control of corruption through improved institutional quality is capable of reducing dollarization and eventually reduces the volatility of the Naira exchange rate. The government should deploy technology, offer incentives and use other control measures to clamp down on the dollarization trend in the country.